Prevalence and Effect of Protozoan Ciliates on eggs, larvae, post larvae, and juvenile stages of Penaeus monodon - LAKSHMI PRASANNA LATHA.B; Dr. D.C. REDDY (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Prevalence and Effect of Protozoan Ciliates on eggs, larvae, post larvae, and juvenile stages of Penaeus monodon